El manual del dictador : por qué la mala conducta es casi siempre buena política - Bueno de Mesquita, Bruce, 1946-; Smith, Alastair, 1967-; Cóndor Orduña, María; Bueno de Mesquita, Bruce, 1946- (Madrid : Siruela, 2013)
Explains the theory of political survival, particularly in cases of dictators and despotic governments, arguing that political leaders seek to stay in power using any means necessary, most commonly by attending to the interests of certain coalitions.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Political leadership -- Philosophy; Power (Social sciences); Political corruption; Electronic books